Effect of Plant Biostimulants on Beetroot Seed Productivity, Germination, and Microgreen Quality - Nadezhda Golubkina; Vladimir Zayachkovsky; Maria Markarova; Mikhail Fedotov; Andrey Alpatov; Lyubov Skrypnik; Sergei Nadezhkin; Otilia Cristina Murariu; Alessio Vincenzo Tallarita; Gianluca Caruso (Crops)
Seed productivity and quality are the bases of modern agriculture. To determine the optimal conditions in terms of seed production and quality, the effect of foliar plant biostimulant treatments (at the beginning and in the middle of the peduncle formation phase and at the beginning of flowering) based on amino acids (Multimolig M and Aminosil), silicon (Si) (Siliplant), selenium (nano-Se), a Rhodotorula glutinis soil yeast formulation, and a fertilizer (Wuxal Macromix), plus an untreated control (only water-sprayed plants), were assessed on Beta vulgaris seed plants grown in an open field in the Moscow region in 2022–2023. Silicon and nano-Se foliar supply led to the highest seed production and viability, as well as positively affecting the yield and quality of the microgreens produced from the latter seeds. Despite the stability of the size distribution of small- and large-sized seeds, only the application of Si increased the occurrence of the large-sized seed class by up to 53%, while R. glutinis fostered a homogenous distribution of seeds among the different diameter classes. The application of all of the biostimulants, except R. glutinis, provided a decrease in oxidative stress in the seeds (reflected in a significant reduction in proline levels), especially for the small-sized seed class, with the highest beneficial effects being caused by Aminosil and Siliplant. All of the treatments were beneficial in terms of chlorophyll and betalain pigment accumulation but did not significantly affect the microgreens’ antioxidant status. The beneficial effect of the biostimulants revealed provides the basis for beetroot seed production and quality improvements to meet the requirements of the Sustainable Development Goals of the United Nations aiming to fight hunger and improve human health and well-being.